Omani Science Teachers’ Perceived Self-Efficacy Beliefs for Teaching Science as Inquiry: Influences of Gender, Teaching Experience, and Preparation Programme - Shahat, M.A.; Ambusaidi, A.K.; Treagust, David (2022)
This study aimed to explore Omani teachers’ self-efficacy beliefs for teaching science as inquiry and investigate the influence of demographic characteristics such as gender, teaching experience, and preparation programme on their beliefs. The study was conducted with a sample of science teachers for grades 5-8 (n=588). Data collected from administering the standardized Teaching Science as Inquiry instrument (TSI) to the sample were analysed using a cross-sectional design. The results showed that teachers perceived themselves as highly successful in teaching science as inquiry. Female teachers had higher perceptions of themselves as highly successful in teaching science regarding Personal Self-efficacy beliefs (PE) and Outcome Expectations (OE) for science teaching as inquiry than male teachers. Moreover, teachers with more teaching experience perceived themselves as more highly successful in teaching science as inquiry than those with less experience. Regarding the type of teacher preparation programme, there was no statistically significant difference in teachers’ self-efficacy beliefs. Omani teachers with more experience teaching science by enquiry reported higher mean scores on teaching science as inquiry. They had higher TSI scores than the teachers with low and moderate experience. Accordingly, new graduate science teachers need to increase their knowledge aspects and practices related to science as inquiry (SI). Therefore, the TSI could be used for science teachers in their training to examine how they conducted teaching science by enquiry in real classroom situations.